A study on development changes in essential oil content and composition in Cymbopogon flexuosus cultivar Suvarna - Gupta, Ashish Kumar; Ganjewala, Deepak (Acta Biologica Szegediensis, 2015)
Cymbopogon flexuosus (Steud.) cv. Suvarna produces an essential oil with unique lemon like aroma which is broadly used in flavors, fragrance, perfumery and pharmaceuticals. Here we report changes in essential oil content and compositions during C. flexuosus cv. Suvarna leaf development, leaf positions and leaf age. Essential oils were isolated by hydro-distillation of leaves harvested at six different developmental stages (10-50 days), 1st-5th leaf positions and three parts (basal, middle and apical) of the leaves. Analyses of essential oils by gas chromatography and GC-MS have identified 20 different terpenoids constituents with citral as the major monoterpene. The study showed that essential oil content was highest in early stages (10-20 days) of leaf development, then declined substantially. Similar pattern of essential oil content was observed between the 1st-5th leaf positions and the basal-apical parts within a leaf. Essential oil compositions were also markedly fluctuated. Percentage together of geranyl acetate and geraniol declined rapidly from 32% to 4% on 10th and 20th days, respectively; while percentage of citral (geranial + neral) increased correspondingly from 56% to 81% on 10th and 20th days, respectively. Similar changes in monoterpene composition were observed in leaf positions and leaf age (basal to apical part). Thus the study revealed that accumulation of essential oil depends on the developmental stages of the concerned plant parts and changes in essential oil content is also reflected by compositional changes in oil constituents.